2009
DOI: 10.1007/s10404-009-0426-5
|View full text |Cite
|
Sign up to set email alerts
|

3D visualization of convection patterns in lab-on-chip with open microfluidic outlet

Abstract: Open-outlet microfluidics is getting more and more attention, thanks to the generation of capillarity-driven flows which simplify the connection with the macroworld. It is known that convection flows are generated at the interface with air, i.e., the meniscus. Several works have investigated evaporation-induced convection, but its effect on particle position control in open-outlet biodevices is still not characterized. In this paper, we present the results of 3D measurement of particle traces near the meniscus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…However, total reflexion and the Fresnel effect will limit the maximum angle. Two mirrors under an angle of 90°were used by Gazzola et al (2009) to track single particles in an open capillary. However, due to image aberrations and the lack of a sophisticated calibration they were just able to visualize the evolving vortex flow.…”
Section: (Scanning) Stereoscopic Imagingmentioning
confidence: 99%
“…However, total reflexion and the Fresnel effect will limit the maximum angle. Two mirrors under an angle of 90°were used by Gazzola et al (2009) to track single particles in an open capillary. However, due to image aberrations and the lack of a sophisticated calibration they were just able to visualize the evolving vortex flow.…”
Section: (Scanning) Stereoscopic Imagingmentioning
confidence: 99%
“…The measured region was not on the meniscus but far away (2-4 times of the channel diameter) from the meniscus. The authors didn't focus on the Marangoni symmetry issue, but it was concluded that the increase of the solute concentration increased both the speed at which the vortex invaded the channel and its flowing speed, which therefore, the solute concentration and buoyancy played a role (Gazzola et al 2009). Most recently in authors' previous work in this journal , a 3D numerical simulation was conducted for a convex meniscus with pure water as working fluid.…”
Section: Introductionmentioning
confidence: 98%
“…Recently Gazzola et al (2009) made a flow measurement in an open microchannel when developing a visualization system. The liquid was saline solution and the meniscus was at the top of the vertical channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently in this journal Gazzola et al (2009) reported an asymmetrical flow pattern generated at a convex meniscus while the boundary conditions were symmetrical. In their experiment a vertical micro well was filled up with liquid and the meniscus was held convex above the well outlet.…”
mentioning
confidence: 97%